Pope Honorius (625–638) – a Pacifist or a Doctrinal Arbiter? - Kashchuk, Oleksandr (Studia Ceranea, 2020)
The purpose of this article is to analyze the standpoint of Pope Honorius (625–638) at the early stage of the controversy over operation in Christ. Patriarch Sophronius (633/634–638) expressed his protest against the statement on one operation in Christ after it had been officially expressed in the Alexandrian Pact of unity in 633. The Pact was supported by both Sergius of Constantinople (610–638) and Emperor Heraclius (610–641). Patriarch Sergius developed his tactics in order to defend the stance of both the Church of Constantinople and the Emperor. As a result, a significant tension between both Patriarchs arose. After the confrontation between Sophronius of Jerusalem and Sergius of Constantinople, Pope Honorius (625–638) was concerned with the matter of operation in Christ. He maintained the standpoint of Sergius and became one of the implicit initiators of the Ekthesis issued by Emperor Heraclius.